1996
DOI: 10.2165/00003495-199652030-00005
|View full text |Cite
|
Sign up to set email alerts
|

Combination Antimicrobial Therapy for Bacterial Infections

Abstract: Therapy with antimicrobial combinations has been used as long as antimicrobials have been available. Combinations of antibiotics are often used to take advantage of different mechanisms of action and/or toxicity profiles. Well established indications for combination antimicrobial therapy include: (a) empirical treatment of life-threatening infections; (b) treatment of polymicrobial infections; (c) prevention of the emergence of bacterial resistance; and (d) for synergism. Disadvantages of combination therapy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
83
0
3

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(91 citation statements)
references
References 99 publications
1
83
0
3
Order By: Relevance
“…The MICs of ampicillin, ciprofloxacin and ceftriaxone were evaluated to be 1 mg ml À1 , 6mg ml À1 and 12 mg ml À1 , respectively. However, according to NCCLS guidelines, S typhimurium was classified as resistant to ceftriaxone and ciprofloxacin, and susceptible to ampicillin as per the MIC breakpoints 10 (for ciprofloxacin and ceftriaxone susceptible (p1), intermediate (1)(2)(3)(4) and resistant (X4), for ampicillin susceptible (p8), intermediate and resistant (X32)).…”
mentioning
confidence: 99%
“…The MICs of ampicillin, ciprofloxacin and ceftriaxone were evaluated to be 1 mg ml À1 , 6mg ml À1 and 12 mg ml À1 , respectively. However, according to NCCLS guidelines, S typhimurium was classified as resistant to ceftriaxone and ciprofloxacin, and susceptible to ampicillin as per the MIC breakpoints 10 (for ciprofloxacin and ceftriaxone susceptible (p1), intermediate (1)(2)(3)(4) and resistant (X4), for ampicillin susceptible (p8), intermediate and resistant (X32)).…”
mentioning
confidence: 99%
“…The treatment can subsequently be adapted according to antibiotic susceptibility test results. The addition of an aminoglycoside to the treatment regimen has many theoretical advantages: (i) a broader spectrum of activity, (ii) increased synergy, (iii) increased bactericidal effect, and (iv) prevention of emergence of resistant strains (26). However, no study that has supported the use of aminoglycosides for the treatment of SGP has been published in the literature (14,15).…”
mentioning
confidence: 99%
“…Because of bacterial resistance against antibiotics and single treatment, using two or more alternative natural product could be interested (Rybak & McGrath, 1996). In the present study all leave extract alone and in combination with each other were revealed antimicrobial activity against all tested bacterial strain, but combination form exhibit more pronounced activity than extract alone.…”
Section: Discussionmentioning
confidence: 50%